Memory culture in the making: the Heidelberg Catechism in the memory of the Dutch Reformed Church (1862-1937) - H. van Tonder (Acta Theologica)
This article explores the Heidelberg Catechism in the memory of the Dutch Reformed Church (DRC) between 1862 and 1937, with specific focus on the events of 1862. By making the Heidelberg Catechism the point of focus the article’s contribution is not by way of answering the “what happened”-questions related to the period, but rather in terms of an analysis of how “what happened” had been remembered over a period of seventy five years by the DRC. In order to do so, the first two sections of the article deals with the theory of memory, the development of memory culture in communities, and the significance of such an analysis for historical thinking. The third part provides four sets of examples of Heidelberg Catechism recollections as a contribution to analyses of the memory culture of the DRC in the late 19th and early 20th centuries.